2020
DOI: 10.15406/unoaj.2020.08.00282
|View full text |Cite
|
Sign up to set email alerts
|

Urinary pathogenic bacterial profile, antibiogram of isolates and associated risk factors among diabetic patients in Hawassa town, southern Ethiopia: a cross-sectional study

Abstract: Urinary tract infection (UTI) is the commonest bacterial infectious disease in community practice with a high rate of morbidity and financial cost. It has been estimated that 150 million people were infected with UTI per annum worldwide which costing global economy more than 6 billion US dollar. In humans, urinary tract is the second commonest site after the respiratory tract, for bacterial infection. Two hundreds forty seven diabetic patients were investigated for UTI using 5 to 10ml midstream urine sample. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The results of antibiotic susceptibility pattern from Otukpo revealed E. coli to be moderately susceptible to streptomycin 60%, cefotaxime 55% and imipenem 50% while at the same time showing moderate to high resistance to cotrimoxazole 50%, tetracycline 55%, ceftriaxone 60%, ciprofloxacin 65%, ofloxacin 70%, nalidixic acid 70%, levofloxacin 80%, aztreonam 80%, ampicillin 80%. This was contrary to a study in India [36] who reported complete sensitivity (100%) to imipenem but comparable resistant pattern has been observed in Ethiopia to nalidixic acid 70% and cotrimoxazole 64.7% [26].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of antibiotic susceptibility pattern from Otukpo revealed E. coli to be moderately susceptible to streptomycin 60%, cefotaxime 55% and imipenem 50% while at the same time showing moderate to high resistance to cotrimoxazole 50%, tetracycline 55%, ceftriaxone 60%, ciprofloxacin 65%, ofloxacin 70%, nalidixic acid 70%, levofloxacin 80%, aztreonam 80%, ampicillin 80%. This was contrary to a study in India [36] who reported complete sensitivity (100%) to imipenem but comparable resistant pattern has been observed in Ethiopia to nalidixic acid 70% and cotrimoxazole 64.7% [26].…”
Section: Discussioncontrasting
confidence: 99%
“…who reported 9.2%,10.1% recorded at Derbe Tabor General Hospital, Northwest Ethiopia[25] and 10.5% in Southern Ethiopia[26]. In contrast, much higher prevalence of 35.3% was reported in Iraq[27] 40.2% in Malaysia[28] and 54.7% in Nepal[29].The prevalence of UTI based on age group showed that age group 46 and 50 had the highest prevalence (33.9%) while age groups 18 and 25, 26 and 30, 31 and 35 had no recorded positive UTI cases.…”
mentioning
confidence: 96%
“…11 In the present study the overall prevalence of significant bacteriuria in diabetic patients was 10.5%. This is similar to the findings reported previously in Addis Ababa (10.9%), 6 Debre Tabor (10.9%) 12 and Romania (10.7%), 13 but lower than a study done in Gondar (17.8%) 4 and other studies done in Sudan (19.5%), 7 Nepal (21%), 14 Iraq (35.3%), 15 and Pakistan (51%). 16 This variation in prevalence might be due to the difference in sample size, geographical location, personal hygiene, and variation in the screening test used.…”
Section: Discussionsupporting
confidence: 88%
“…4 In other hand it is contradicting with a study done in Addis Ababa 28%, 6 Sudan (23%), Uganda (28.6%), India (20%), Iraq (15.1%) and Nepal (21.6%). 7,11,15,21,22 The higher isolation rate of CONs in this study could be change in pattern of infection in diabetic patients. 11 In the present study BMI >=30kg/m 2 was 14 times more likely to develop significant bacteriuria (AOR=14.44; 95%CI=3.55-58.77; p<0.01).…”
Section: Discussionmentioning
confidence: 66%
“…The sample size was calculated based on a single sample size estimation using the prevalence of 10.5% indicated in the study done in Ethiopia, 27 with an expected margin of error taken at 5% and a confidence interval of 95% and 10% contingency for the non-respondent. The calculated sample size was 158.…”
Section: Study Population and Sampling Techniquementioning
confidence: 99%